REVIEWING THE ROLE OF PARENTS IN ELEMENTARY SCHOOL STUDENTS' LEARNING IN THE PANDEMIC ERA - Arif Widodo; Prayogi Dwina Angga; Muhammad Syazali; Umar Umar (Jurnal Eduscience, 2023)
One of the consequences of limiting face-to-face learning in the pandemic era is the implementation of distance learning. At the elementary school level, the application of distance learning is carried out in various ways, one of which is by applying online learning. This article aims to analyze how important the role of parents in learning for elementary school-aged children is in the pandemic era. This research method uses a literature study approach. Data was collected by browsing research articles through Google Scholar. The article analyzed is a research article that discusses the involvement of parents in distance learning in the pandemic era. The results of the analysis of various kinds of literature show how important the role of parents in supporting the online learning process is. In online learning, the learning process cannot run optimally without collaboration between teachers and parents. Most of the teacher's tasks in online learning have been taken over by parents. Parents function as facilitators, motivators, and become the main guides in the learning process. Another role that is no less important than parents is as a learning supervisor, through this supervision control of the quality of learning can be carried out even though it is constrained by distance from the school